Deconvolution of sarcoma methylomes reveals varying degrees of immune cell infiltrates with association to genomic aberrations - Simon, Malte; Mughal, Sadaf Shabbir; Horak, Peter; Uhrig, Sebastian; Buchloh, Jonas; Aybey, Bogac; Stenzinger, Albrecht; Glimm, Hanno; Fröhling, Stefan; Brors, Benedikt; Imbusch, Charles (Journal of translational medicine, 2021)
Soft-tissue sarcomas (STS) are a heterogeneous group of mesenchymal tumors for which response to immunotherapies is not well established. Therefore, it is important to risk-stratify and identify STS patients who will most likely benefit from these treatments.
Gesehen am 20.07.2021